Evaluation of a Titanium Surface Treated with Hydroxyapatite Nanocrystals on Osteoblastic Cell Behavior: An In Vitro Study - Martinez, Elizabeth Ferreira; Ishikawa, Guilherme Junji; Lemos, Alexandre Barboza de; Barbosa Bezerra, Fabio Jose [UNESP]; Sperandio, Marcelo; Napimoga, Marcelo Henrique (Quintessence Publishing Co Inc, 2018)
Purpose: In the context of macrostructural and microstructural modifications to the design of dental implants, surface topography changes with different treatments have the purpose of accelerating bone formation. The aim of this study was to evaluate in vitro the influence of aggregated hydroxyapatite nanocrystals to surfaces treated with double acid etching (Nano) on osteoblastic cell behavior compared with a conventional double acid-etched surface (DE). Materials and Methods: Commercially pure Grade 4 titanium discs (6 x 2 mm) were selected, and both cell proliferation and viability were assessed at 24, 48, and 72 hours using Trypan blue vital dye and MTT, respectively. The expression of type I collagen and osteopontin on such surfaces was evaluated using ELISA. Immunostaining for fibronectin was also performed. Quantitative data were analyzed statistically using two-way analysis of variance (ANOVA) followed by Bonferroni post-test with a 5% significance level. Results: The results showed that in all evaluated time periods, cells expressed fibronectin on both surfaces. The cells presented greater morphologic spreading on the Nano surface when compared with the conventional DE surface in all assessed times. Increased cell proliferation and viability were detected in the Nano surface (P < .05) when compared with the conventional DE surface, especially after 72 hours. Osteopontin expression was higher after 24 hours in the Nano surface when compared with the conventional DE surface (P < .05). For type I collagen, a higher expression was observed with the Nano surface than with the DE surface, again after 72 hours (P < .05). Conclusion: This in vitro study showed that the treated Nano surface tested promoted increased cell proliferation and viability when compared with the control surface. Additionally, increased cell spreading as well as type I collagen and osteopontin secretion were observed, favoring the early events of osseointegration.
Keywords: osseointegrated dental implant; osseointegration; physical-chemical treatment